THE LEGAL CERTAINTY OF LAND OWNERSHIP RIGHT IN REGISTRATION’S CONTEXT - Christiana Sri Murni; Bernadus Basa Kelen; Sumirahayu Sulaiman (International Journal of Law Reconstruction, 2022)
The aims of this research is to know that certificate as a letter of evidence that is valid as strong evidence regarding the physical data and juridical data contained in it, as long as the physical data and juridical data are in accordance with the data contained in the letter of measurement and the book of land rights in question. But in reality, the certificate can still be sued by the subject of the right who feels he has the right to the land. This research used a normative legal research with qualitative descriptive data analysis. Based on the results of the study indicate that land registration activities include the collection and processing of physical data, proof of rights, bookkeeping, and issuance of certificates. With the issuance of a certificate of land rights, the owner has legal certainty and legal protection. However, in reality, land rights certificates can be sued in court. This shows the existence of legal uncertainty, because at any time the rights subject who feels he has a right or feels that his rights have been violated by another party can file a lawsuit against another party whose name has been registered in a certificate.